Application of At Thoriqoh Al Mubasyiroh to Increase Maharoh Al Kalam for Madrasah Aliyah Students: Penerapan At Thoriqoh Al Mubasyiroh untuk Meningkatkan Maharoh Al Kalam Siswa Madrasah Aliah - Handayani, Ardiana; Fauji, Imam (Indonesian Journal of Education Methods Development, 2022)
This article aims to determine the application of at thoriqoh al mubasyiroh to increase maharoh al kalam for class X students ma Minhajul Muna Ponorogo. The research method used is collaborative experimental classroom action research. The research approach in this study uses a qualitative and quantitative approach. Data collection techniques used are test, observation, and documentation techniques. And as for the data analysis technique used is drawing conclusions and analysis in the form of numbers. And based on the results obtained by the researchers as follows, the application of the Al Mubasyiroh method in learning speaking skills in class 10 was successful. This can be seen from the results of the application of the method in the second cycle, namely with a class average value of 88 with a percentage of 75% of which more than 70% of students are able to achieve the KKM, the application of the Al Mubasyiroh method can be done to improve speaking skills in class 10 in MA Minhajul Muna